MT conductivity signatures of mineral systems: 3D MT over the Eastern Goldfields Super Terrane, Yilgarn Craton. Issue 1 (1st December 2019) - Selway, Kate; Dentith, Mike; Özaydın, Sinan
Summary: Magnetotellurics (MT) is emerging as a key tool for understanding giant mineral systems. For MT to be effective in mineral exploration we require both an improved understanding of the causes of electrical conductivity anomalies and an increased number of surveys over known mineral deposits. We present results from a new, lithospheric-scale 3D MT dataset collected in the southern Yilgarn Craton, Western Australia. This 250x250 km survey covers the western Eastern Goldfields Super Terrane and the world-class Kambalda nickel and Kalgoorlie gold deposits. We interpret the electrical conductivity models using experimental electrical conductivity data to link the MT results to a mineral systems analysis.